2022
DOI: 10.3389/fbioe.2022.925841
|View full text |Cite
|
Sign up to set email alerts
|

Targeting regulation of stem cell exosomes: Exploring novel strategies for aseptic loosening of joint prosthesis

Abstract: Periprosthetic osteolysis is a major long-term complication of total joint replacement. A series of biological reactions caused by the interaction of wear particles at the prosthesis bone interface and surrounding bone tissue cells after artificial joint replacement are vital reasons for aseptic loosening. Disorder of bone metabolism and aseptic inflammation induced by wear particles are involved in the occurrence and development of aseptic loosening of the prosthesis. Promoting osteogenesis and angiogenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…New studies have also shown that MSCs can inhibit osteoclasts, and stem cell exosomes can block osteoclast activation or differentiate into osteoblasts to regulate bone remodeling. BMSC derived exosomes have been demonstrated to activate osteogenesis and downregulate osteoclastogenesis through multiple pathways ( Ma et al., 2022 ).…”
Section: Cell-cell Interactionmentioning
confidence: 99%
“…New studies have also shown that MSCs can inhibit osteoclasts, and stem cell exosomes can block osteoclast activation or differentiate into osteoblasts to regulate bone remodeling. BMSC derived exosomes have been demonstrated to activate osteogenesis and downregulate osteoclastogenesis through multiple pathways ( Ma et al., 2022 ).…”
Section: Cell-cell Interactionmentioning
confidence: 99%
“…Consequently, accumulating particle debris activates macrophages CD68 + (45, 88, 98-100). The activation of macrophages at the implant-tissue interface can occur by "failed phagocytosis" of indigestible wear particles to become foreign body giant cells (4,24,76,98,101) or by cell contact through toll-like receptors (TLRs) 2 and 4, CD11b, and CD14 (4,22,38,102). In aseptic loosening, the immune reaction was usually observed in synovial membrane-line interface tissues by co-localizing polymeric particles and macrophages (97, 98, 103).…”
Section: Macrophages and Periprosthetic Osteolysismentioning
confidence: 99%
“…The macrophage activation results in the release of inflammatory cytokines, chemokines, reactive oxygen species (ROS), tumor necrosis factor-a (TNF-a), interleukin (IL)-1b, IL-6, IL-17, and interferon-g (IFN-g), which are potent contributors to bone resorption (2,4,22,102,(104)(105)(106)(107)(108). TLRs and nucleotide-binding oligomerization domain (NOD)-like receptors (NLRs) can recognize exogenous pathogenassociated molecular patterns (PAMPs) and endogenous molecules created during inflammation and tissue remodeling.…”
Section: Macrophages and Periprosthetic Osteolysismentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical strength of metal materials is closer to that of human bones, which makes metal materials ideal for the reconstruction of human mechanics. At present, after many years of clinical application of orthopedic metal materials for medical use, there are still many problems, such as autoimmune reaction after material implantation, mismatch between elastic modulus and host bone, nonfusion between bone and interface, as well as the impact of metal corrosion and wear [ 4 , 5 ].…”
mentioning
confidence: 99%